2019
DOI: 10.3390/ijms20246271
|View full text |Cite
|
Sign up to set email alerts
|

Biofilms Positively Contribute to Bacillus amyloliquefaciens 54-induced Drought Tolerance in Tomato Plants

Abstract: Drought stress is a major obstacle to agriculture. Although many studies have reported on plant drought tolerance achieved via genetic modification, application of plant growth-promoting rhizobacteria (PGPR) to achieve tolerance has rarely been studied. In this study, the ability of three isolates, including Bacillus amyloliquefaciens 54, from 30 potential PGPR to induce drought tolerance in tomato plants was examined via greenhouse screening. The results indicated that B. amyloliquefaciens 54 significantly en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 77 publications
(46 reference statements)
1
18
0
1
Order By: Relevance
“…Plants that were inoculated with mutants capable of hyper-robust biofilm formation (ΔabrB and ΔywcC) were found to demonstrate drought resistance as compared to plants that were inoculated with mutants having biofilm formation defects (ΔepsA-O and ΔtasA) which could not grow in water deficit conditions. Therefore, these studies confirm that the ability to form biofilms helped the B. amyloliquefaciens 54 strain enhance drought tolerance of tomato plant [67].…”
Section: Fig 2 Roles Of Eps Microbial Exopolysaccharides In Mitigation Of Abiotic Stress and Plant Growth Promotionsupporting
confidence: 64%
“…Plants that were inoculated with mutants capable of hyper-robust biofilm formation (ΔabrB and ΔywcC) were found to demonstrate drought resistance as compared to plants that were inoculated with mutants having biofilm formation defects (ΔepsA-O and ΔtasA) which could not grow in water deficit conditions. Therefore, these studies confirm that the ability to form biofilms helped the B. amyloliquefaciens 54 strain enhance drought tolerance of tomato plant [67].…”
Section: Fig 2 Roles Of Eps Microbial Exopolysaccharides In Mitigation Of Abiotic Stress and Plant Growth Promotionsupporting
confidence: 64%
“…Furthermore, adhesion of particles to each other or to a target site is a central aim in different applications. ii. Protection from environment: Biofilms help microorganisms to protect themselves in extreme environments (Yin et al ., 2019), against ultraviolet radiation (UV) (de Carvalho, 2017), extreme temperatures (Smith et al ., 2016; Kent et al ., 2018), pH variations (Narayanan et al ., 2016), salinity or drought stress (Alaa, 2018; Wang et al ., 2019) and limitation of nutrients (Gingichashvili et al ., 2020). In general, a biofilm can be described as a protective matrix in which both the polysaccharide‐producing microorganisms and co‐living cells are encapsulated.…”
Section: Microbial Polysaccharides: Functionalities and Their Applicability In Industrymentioning
confidence: 99%
“…is the ability of biofilm formation on plants' surfaces. In a recent report, Wang et al (220) demonstrated that B. amyloliquefaciens 54 inoculation in tomato exerts drought tolerance in plants through enhanced expression levels of stressresponsive genes, such as lea, tdi65, and ltpg2 in the treated plants. Enhancement of drought tolerance was also linked to the enhancement of survival rate, relative water content and root vigor in tomato.…”
Section: Drought Tolerancementioning
confidence: 99%
“…Biofilm forming ability of Bacillus bacteria was positively correlated with plant root colonization. Interestingly, plants inoculated with hyper-robust biofilm-forming (ΔabrB and ΔywcC) mutants were better able to resist drought stress compared to defective biofilm mutants (220). Although a large body of literature is available on the enhancement of drought tolerance in plants by plantassociated bacilli, precise mechanisms of their beneficial actions in plants are still poorly understood.…”
Section: Drought Tolerancementioning
confidence: 99%
See 1 more Smart Citation